Short-term changes in renal function in children and adolescents undergoing extracorporeal shock wave lithotripsy - Emir Milišić; Zlatan Zvizdić; Asmir Jonuzi; Edin Begić; Lejla Milišić; Amira Mešić (Medicinski glasnik, 2019)
Aim: To identify short-term effects of extracorporeal shock wave lithotripsy (ESWL) on renal function in children and adolescents with single kidney stones. Methods: In a 4-year period 30 children (15 boys and 15 girls) from 10 to 18 years of age were treated for unilateral renal stones with ESWL. Inclusion criteria were: up to 18 years of age, kidney stone (from 4 to 20 mm in diameter) visible on X-ray, first ESWL treatment, unilateral lithotripsy treatment without previous kidney surgery, patients without infravesical obstruction, patients without proven urinary infection, repeated use of one (the same) analgesic, patients without anticoagulant and antihypertensive therapy, patients without use of nephrotoxic drugs prior to and during the treatment, normal blood pressure, non-pregnancy patients with normal renal function. Serum enzymes (alkaline phosphatase, lactate dehydrogenase), cystatin C, serum and urine electrolytes (sodium, potassium, chloride), and urine neutrophil gelatinase-associated lipocalin (uNGAL) were tested before, on the first and fifth day after the treatment. Results: An increase of alkaline phosphatase and lactate dehydrogenase was statistically significant on day 1 (p<0.05) and values returned to normal on day 5. Serum cystatin C level was also significantly increased during the first four days after ESWL treatment (p<0.05) and returned to baseline on post-treatment day 5. There was a statistically significant difference in the level of uNGAL in urine before and 24 hours after ESWL treatment (p<0.05). Conclusion: The ESWL is a safe and curative procedure for the treatment of kidney stones in children and adolescents with no evidence of serious adverse effects on renal function.
Keywords: electrolytes; lithotripsy; urolithiasis